Restorative potential of an in-campus ecological wetland: biodiversity and water quality assessment - Yusof, Alia Amira (Universiti Sains Malaysia, 2014)
Constructed wetlands are ecological wetlands designed for the removal of a wide range of pollutants in the natural water bodies, and enhance the abundance of biodiversity on the ecosystem. This study was conducted from December 2013 till February 2014 to examine the potential ecological wetland in in-campus for water quality improvement and biodiversity conservation. Water quality samplings were carried out via in-situ and lab analysis, while the potential for biodiversity conservation was evaluated by on-site monitoring and identification of bird, plants, fish and phytoplankton. Results showed that the water quality discharge to the Kerian River was classified into class I or class 11 classification that is suitable for sensitive aquatic species. Result revealed that the constructed wetland removed approximately 63.29%,59.19%. 30.84% and 24.28% of the total suspended solid (TSS), ammonical nitrogen (AN), biochemical oxygen demand (BOD5) and chemical oxygen demand (COD), respectively. The value of water quality index (WQI) indicated that the performance for water quality improvement followed the order dry season> wet-dry season > wet season. Six plant species were identified on the constructed wetland. Lepironia articulata> Phragmites karka> Scirpus grossus> Eleocharis variegata> Typha angustifolia> Hanguana malayana. with the distribution of 45%. 25%, 15%, 7%, 6%, and 2%, respectively. Twenty-one bird species from 12 different families were identified. Eight classes of phytoplankton was found, with order Chlorophyceae> Cyanophyceae> Zygnematophyceae> ZygnemophyceaO Scenedesmaceae> Coscinodiscaeae> Bacillariophyceae> Trihonemataceae. and distributions of 35%. 27%. 1 1%. 8%. 7%, 5%. 4% and 3%. respectively. Nine fish species was found, with the highest composition of Oreochromis niloticus. which constituted 27.27% of constructed wetland. The lowest species was Channa striata and Pangasius spp., with 2.27% of the fish species. These fish species were abundantly found at the micropool. This study proved that the in-campus constructed wetland is suitable for the water treatment and biodiversity conservation.